REAP (READ, ENCODE, ANNOTATE, AND PONDER) STRATEGY COMBINED WITH MIND MAPPING TO FACILITATE STUDENTS’ READING COMPREHENSION - Paula Eka Ramdhani; Ririn Pusparini (STKIP Siliwangi, 2022)
REAP (Read, Encode, Annotate, Ponder) strategy is a well-designed learning strategy for teaching students to comprehend a reading text. The aim of this study is not only to present how the REAP strategy is implemented in reading, especially in narrative texts but also it describes how the mind mapping emerged in the REAP strategy to boost students’ interest and makes the reading activity more enjoyable. This study was carried out in the eleventh grade at one of Sidoarjo's private senior high schools which were consisting of thirteen students. Furthermore, the interpretive descriptive qualitative research design through observation and document analysis was used as the base of this study. This study also showed that there are several stages in the implementation of REAP strategy combined with mind mapping for facilitating students’ reading comprehension such as preparing the classroom environment, brainstorming, making group discussion, reading the story, encoding the difficult vocabulary, annotating the important point, pondering the moral value, and presenting students’ mind mapping. The results discovered that in the teaching and learning process, the students were able to comprehend the narrative text successfully. It also made reading activity more alive, activates background knowledge among students, and encourages them to think creatively.